Effects of halophilic peptide fusion on solubility, stability, and catalytic performance of D-phenylglycine aminotransferase - Hossein Javid (2018)
D-Phenylglycine aminotransferase (D-PhgAT) from Pseudomonas stutzeri ST-201 is useful for enzymatic synthesis of enantiomerically pure D-phenylglycine. However, its low protein solubility prevents its application at high substrate concentration. With an aim to increase the protein solubility, the N-terminus of D-PhgAT was genetically fused with short peptides (A1 α-helix, A2 α-helix, and ALAL, which is a hybrid of A1 and A2) from a ferredoxin enzyme of a halophilic archaeon, Halobacterium salinarum. The fused enzymes A1-D-PhgAT, A2-D-PhgAT, and ALAL-D-PhgAT displayed a reduced pI and increased in solubility by 6.1-, 5.3-, and 8.1-fold in TEMP (pH 7.6) storage, respectively, and 5-, 4.5-, and 5.9-fold in CAPSO (pH 9.5) reaction buffers, respectively, compared with the wild-type enzyme (WT-D-PhgAT). In addition, all the fused D-PhgAT displayed higher enzymatic reaction rates than the WT-DPhgAT at all concentrations of L-glutamate monosodium salt used. The highest rate, 23.82 ± 1.47 mM/h, was that obtained from having ALAL-D-PhgAT reacted with 1,500 mM of the substrate. Moreover, the halophilic fusion significantly increased the tolerance of D-PhgAT in the presence of NaCl and KCl, being slightly in favor of KCl, where under the same condition at 3.5 M NaCl or KCl all halophilic-fused variants showed higher activity than WT-D-PhgAT. © 2014 by The Korean Society for Microbiology and Biotechnology.